The Existence Of Modern Maskets On Social Economic Conditions Of Traditional Market Traders Karisa In Jeneponto District - Abdul Rahman; Hakim Maksud; Idrus Idrus (Trunojoyo University of Madura, 2022)
This study aims to determine how big the existence of the consequences since the existence of modern markets or minimarkets on the socio-economic conditions of traders in traditional markets in Jeneponto Regency, South Sulawesi Province. In relation to this research, there are two main variables, namely the existence of a modern market and the socio-economic conditions of traders. The method used in this research is a survey method with a descriptive quantitative approach. The population used is the traders in the Karissa Market, Jeneponto Regency, 35 samples taken by chance or incidental sampling as desired or quota sampling . Hypothesis testing uses product moment, coefficient of determination test and alpha reliability test. Collecting data using a questionnaire technique of questions about the modern market and the socio-economic conditions of traders at the Karissa Traditional Market in Jeneponto Regency. The findings indicate that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, meaning that there is an influence of the existence of a modern market on the socio-economic conditions of the Karissa Traditional Market traders in Jeneponto Regency.